Methods for Dynamic Spectrum Access and Spectrum Management in Cognitive Radios - Marco di Marzo, Gian; Benedetto, Francesco (Recent Patents on Computer Science, 2013)
Radio Communication is one of the research fields that is continuously improving and innovating. In particular, cognitive radio is one of the fastest developing arguments over the last few years, due to recently published standards that were lacking some years ago. The possibility of understanding the best frequency to be used is an important discovery in the world of communications. In this work, we will see how the cognitive technology works when has to access the spectrum. We will discuss and review some recent patents focusing on the following topics: how the system recognizes the best frequency, and how it changes the frequencies to log on the spectrum. At the end of the paper, we will discuss the importance of this new methodology along with future developments, keeping in view the pros and cons.
Keywords: primary user detection